(untitled) (Al-Aasar, 2025)
Access to justice remains a fundamental pillar for the rule of law and equitable societies worldwide. In the 21st century, technological advancements present transformative opportunities to enhance the delivery and accessibility of justice systems. This article explores how emerging technologies, such as artificial intelligence, blockchain, online dispute resolution, and digital courts, are reshaping legal landscapes globally, with a focus on both developed and developing countries, including Pakistan and other third-world contexts. The study reviews existing literature on access to justice challenges and technology integration, discusses the benefits and pitfalls of digital justice systems, and evaluates real-world applications through case studies. The article also addresses barriers including digital divides, data privacy, and regulatory constraints. Statistical data and comparative analysis illustrate technology’s impact on case resolution speed, cost efficiency, and inclusivity. Policy recommendations are provided for governments, legal practitioners, and civil society to foster equitable and effective justice through technology. This comprehensive review aims to contribute to ongoing legal reforms and encourage innovation while safeguarding fundamental rights.